2017
DOI: 10.3390/w9100757
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Nitrate Removal from Aqueous Solution by Modified Steel Slag

Abstract: Steel slag, which makes up a gigantic amount of metallurgical industrial solid waste, was in this experiment successfully synthesized an inexpensive adsorbent used to remove nitrate pollution from aqueous solution. This adsorbent was obtained by mixing steel slag, aluminium hydroxide and deionized water, and aging this at a mass ratio of 3:0.45:2, and then activating it at 800 • C. The physicochemical characteristics of the steel slag before and after modification were investigated to compare the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…Thermal activation involves purposeful heat treatment, with and without additives, to increase the amount of crystalline phases in solidified slags. To date, extensive studies have highlighted the benefits of activation of slags for use in the adsorption of cations and anions from industrial effluents and wastewaters [42,57,[59][60][61][62][63][64][65][66]139,140]. In particular, Yang et al [139] investigated the effect of nitrate removal by thermally activated steelmaking slags mixed with Al(OH) 3 .…”
Section: Thermal Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal activation involves purposeful heat treatment, with and without additives, to increase the amount of crystalline phases in solidified slags. To date, extensive studies have highlighted the benefits of activation of slags for use in the adsorption of cations and anions from industrial effluents and wastewaters [42,57,[59][60][61][62][63][64][65][66]139,140]. In particular, Yang et al [139] investigated the effect of nitrate removal by thermally activated steelmaking slags mixed with Al(OH) 3 .…”
Section: Thermal Activationmentioning
confidence: 99%
“…The performance of slags modified at 800 • C was 1.9 times higher than that of unmodified slags. The superior performance was attributed to a 3.34-fold increase in specific surface area and a 2-fold increase in the total pore volume of thermally modified slags [139]. Islam and Patel [60] observed an increase in porosity from 9.74% to 17.89%, and in specific surface area from 5.62 m 2 g −1 to 40.89 m 2 g −1 , in BOF slags thermally activated at 1000 • C for 24 h. The fluoride adoption capacity of the thermally activated slags was also significantly higher than that of un-activated slags [60].…”
Section: Thermal Activationmentioning
confidence: 99%
“…To check enhancement in the adsorption capacity of the synthesized beads, it was compared with adsorbents in the market (Table S5). It was found that the reported adsorbents exhibit a considerable adsorption capacity, and among them, the metal-ion-loaded AlgBT composite beads had an enhanced adsorption capacity on NO 3 – removal. Moreover, in this study, the adsorbents produced in the form of composite beads, which possess a higher stability compared with the powder form of adsorbents.…”
Section: Resultsmentioning
confidence: 99%
“…The Zn 3 Al-Cl-LDH is contacted with a potassium nitrate solution (0.4 g/L) for 5 min, 10 min, 20 min, 30 min, and 60 min. Before washing Zn 3 Al-Cl-LDH after [22]. adsorption and which is intended for the dielectric analysis.…”
Section: Assays Of Nitrate Ions In Balancementioning
confidence: 99%